Work-related stressors and coping strategies during COVID-19 pandemic: A qualitative study on reflections of frontline health care workers from India - Mukhopadhyay , Prianka; Pal, Ranabir; Hassan, Sk. Kamal; Sarkar, Manisha (Social Determinants of Health, 2023)
Background: Frontline healthcare workers, a vital workforce in developing countries is often out of mainstream vision and their challenges and coping behaviors under stressful conditions remain unclear to stakeholders. This study was undertaken with the objective to explore the challenges faced by community surveillance workers and their coping strategies during COVID-19 pandemic. Methods: A qualitative descriptive study with constructivism paradigm was undertaken for a period of one year by conducting eight focus group discussions and eight in-depth interviews among the health workers undertaking COVID-19 surveillance selected purposively from eight wards within three Boroughs of a Municipal Corporation using interview guide. Thematic analysis was used to compare and contrast the codes to generate themes inductively under two constructs. Results: The first construct, factors influencing work related stress was categorized into four themes related to- work environment, community’s response towards pandemic surveillance, organizational support and personal factors. Main predisposing factors of work place stress were risk of self-infection, concern for family safety, inadequate training, shortage of manpower and protective equipment etc. While a strong commitment towards work, assistance from local community influencers, administrative appreciation and supportive supervision were protective factors against stress. Second construct on coping strategies was categorized into managing stress by problem-focused strategies like adapting with experience, gathering information and sharing experiences, adopting self-care practices; while emotion-based coping strategies included denial, venting out, or turning to religion etc. Conclusion: Community surveillance workers faced considerable and variable stress during pandemics due to various underlying work stressors, managed innovatively, using self-coping strategies.